Penerapan Budaya Literasi untuk Membentuk Karakter Siswa Kelas V Melalui Gerakan Literasi Sekolah (GLS) di SD Negeri Karangrejo 02 - Wulandari, Anggita; Sulianto, Joko; Patonah, Siti; Yoganingsih, Chadwandwi (Melati Institute, 2024)
The lack of student interest in reading can lead to a decline in insight and knowledge. The implementation of the School Literacy Movement (GLS) at SDN Karangrejo 02 aims to increase students' interest in reading. This study used a qualitative approach using descriptive methods. The study population included all grade V students of SDN Karangrejo 02 for the 2023/2024 school year. The research sample involved grade V students, grade V homeroom teachers, and the principal of SDN Karangrejo 02 who were interviewed. Data collection techniques in this study were observation, interview, questionnaire, and documentation. From the results of the analysis in the application of reading literacy culture and interviews in this study, it shows that the School Literacy Movement (GLS) at school is very effective in improving students' reading skills.